If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + x + -2 = -6x + x + -4 Reorder the terms: 5 + -2 + x = -6x + x + -4 Combine like terms: 5 + -2 = 3 3 + x = -6x + x + -4 Reorder the terms: 3 + x = -4 + -6x + x Combine like terms: -6x + x = -5x 3 + x = -4 + -5x Solving 3 + x = -4 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 3 + x + 5x = -4 + -5x + 5x Combine like terms: x + 5x = 6x 3 + 6x = -4 + -5x + 5x Combine like terms: -5x + 5x = 0 3 + 6x = -4 + 0 3 + 6x = -4 Add '-3' to each side of the equation. 3 + -3 + 6x = -4 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = -4 + -3 6x = -4 + -3 Combine like terms: -4 + -3 = -7 6x = -7 Divide each side by '6'. x = -1.166666667 Simplifying x = -1.166666667
| log(x+1)=20 | | 3+2x+7x=39 | | 22+17=d-17 | | x-4+5x=-2x+1+9x | | 9-3x=(-x)+1+2x | | 5.3x+100=28.09+10x | | 2x+3-6=x+8-7x | | 29+4a=7(a+2) | | 4x^2-12x-7=9 | | 16=2/5c | | 7(y-4)/4=2y-4 | | 4+2t-3=8t+19-4t | | 19-13w= | | c=.2x^2-98x+12590 | | 7z-(3z-3)=3+2z | | 5x(2y)=435 | | 10(t-2)+8t=6(3t+4)-13 | | -5x-1=x+7 | | 4x-3(1-x)=-15+5x | | -2x+7(3x-1)=32 | | 30kx-6kx=8forx | | f(x)=2x+11-3 | | 5x-15=11+3x | | 4b+2=27 | | 9x-21=15+11x | | 15x=87 | | x-2.97=5.9 | | 5(2x-3)-3(x-7)=5 | | 2x+3=8x-1+6 | | .04(8x-3)=.32(x+7)-2.36 | | 3=6(x-1)+y | | 8x^2=26 |